Inter-language Pragmatics: Recent Insights and Applications in Cross-Cultural Communication - Yadav, Aditya Kumar (Journal of Advanced Research in English & Education; Vol 9 No 4 (2024): Journal of Advanced Research in English and Education, 2024)
Inter-language pragmatics (ILP) is an evolving and interdisciplinary field of study that focuses on how non-native speakers acquire and utilize pragmatic competence in a second or foreign language. Pragmatic competence encompasses the ability to understand and use language in context, considering the social, cultural, and interpersonal aspects of communication. As globalization facilitates greater cross-cultural communication, understanding the pragmatic nuances that exist across different languages and cultures has become increasingly critical. The ability to effectively navigate these nuances is essential for minimizing misunderstandings, improving interpersonal relations, and achieving communicative success in diverse settings. This review article explores recent advancements in the study of inter-language pragmatics, particularly focusing on its practical application in cross-cultural communication. Drawing on a range of studies, we analyze the development of pragmatic competence among second language learners, highlighting the challenges and strategies involved in acquiring cultural and contextual awareness. We examine how intercultural competence influences communication strategies, with a particular focus on the ways in which learners adjust their language use in response to different cultural expectations. Furthermore, we delve into the phenomenon of pragmatic failures—situations where learners’ communication results in misunderstandings due to mismatched cultural norms or inappropriate use of language forms. The article also discusses how these failures can be mitigated through awareness-raising activities and pragmatic training in language education. The review additionally addresses the influence of various cultural variables, such as politeness strategies, indirectness, formality, and social hierarchies, on intercultural exchanges. The findings suggest that developing a nuanced understanding of cultural differences is crucial for effective communication, especially in professional, diplomatic, and educational settings. Ultimately, the article underscores the importance of integrating intercultural communication skills and pragmatic awareness into language learning programs, ensuring that learners are equipped not only with linguistic competence but also with the ability to navigate the complex social and cultural dynamics of real-world communication.